How Do Children Reason About Mirrors? A Comparison Between Adults, Typically Developed Children, and Children With Autism Spectrum Disorder - Soranzo, Alessandro; Bertamini, Marco; Cassidy, Sarah (Frontiers in Psychology, 2021)
The information about what one can see, and what other people can see from different viewpoints is important. There are circumstances in which adults and children make systematic errors when predicting what is visible from their own or others’ viewpoints. This happens for example when reasoning about mirrors. We explored differences among three developmental groups: young adults (N=60) typically developing children (N=30); and children with Autism Spectrum Disorder (ASD, N=30). We used an illustration of a top-down view of a room with a mirror on a wall (Room Observer and Mirror Perspective test: ROMP). Participants selected (circled on paper) which objects behind the observer in the room were visible, reflected from the mirror, from a given position (viewpoint). For half of each group the observer in the room was described as a teddy-bear; for the other half it was described as a child. Overall, there were many errors in all groups, which we separate in errors of ignoring the viewpoint (same response to all three locations) and inversion errors (choosing objects on the left instead of the right or vice versa). In addition to the overall task difficulty, the ASD group made relatively more mistakes of ignoring the viewpoint compared to the other groups, and underestimated how many objects were visible in the teddy bear condition; i.e. when the viewpoint was an inanimate object. We suggest that this is related to a delay in theory of mind development (Baron-Cohen et al., 1985).